Comparative study on the impact of leadership styles on employee job satisfaction in private and public banking sector organizations; with special reference to vauniya district - Mathushan, P.; Sarawanabavan, A. (University of Jaffna, 2019)
Generally, the leadership styles of leaders influence employee job satisfaction in the organizations. Bank managers can affect employee’s job satisfaction, by following appropriate leadership styles. The previous studies confirm that the leadership styles create environments in the organizations by influence employee job attitude. Competitiveness in the banking sector specifically private and public banks are higher in Sri Lanka and banks have to focus on quality customer service to attract more loyal customers. This require more satisfied employee base to provide higher service level. The main objective of the research is to test two different leadership styles and its influence on satisfaction of bankingemployees. TheleadershipstylesareTransactionalandTransformationalleadership style and job satisfaction factors which affect the two different leadership styles. For the purpose of this study, 150 questionnaires distributed through the method of simple random sampling among public bank and private banks in Vavuniya district. From the selected sample, there were only 105 questionnaires completed and usable and returned. Correlation and regression analysis were done to test the hypotheses. The finding of this study indicated that transformational leadership has a strong positive relationship with employee job satisfaction.Further the study foundthat transactional leadership has a moderate positive relationship with employee job satisfaction in banking sector.
Keywords: Transformational leadership; Transactional leadership; Job satisfaction; Banking sector